Addressing trauma and empowering students through school-based mindfulness practices - Kraemer-Holland, Angela (Contemporary justice review, 2021)
This article defines mindfulness and trauma, and explores the benefits of a mindfulness practice in classroom settings to empower students socially, emotionally, and physically. More specifically, this article explores the implementation and benefits of a mindfulness practice in academic settings, especially to address trauma, highlighting the benefits of Transformative Life Skills (or TLS) as a formal mindfulness practice to institute in educational institutions. Finally, this article addresses possible challenges with implementing mindfulness strategies in schools and the need for increased research illustrating the impact of mindfulness practices on student populations who have faced trauma.